In vitro analysis of the antifungical activity of plant extracts against yeasts belongimg to the Candida albicans species (Research, Society and Development, 2021)
Candidiasis is one of the most common affections, and it is estimated that most women will present, throughout their lives, at least one episode of the infection. And with this the importance of studies on other alternative methods for treatment based on plant extracts, which have ecological potential to replace the use of synthetic products. Thus, the research aimed to analyze the antifungal activity of crude extracts of the vegetables Morinda citrifolia (None), Caryocar brasiliense (Pequi), Annona muricata (Graviola), Morus alba L. (Mora) and Apis mellifera L. (Propolis) in front of the yeast Candida albicans. The vegetables were collected in the municipality of Teresina-PI and dried at room temperature in the shade, with daily exposure of 4 h; milled in knife mills; the extracts were obtained in methanol and the susceptibility tests were carried out in triplicate on agar-agar and Muller-Hinton agar culture media, using the agar diffusion technique. The Candida albicans ATCC-76485 strain was used in the tests. Of the five vegetables used, the extracts of Pequi and Propolis, showed antifungal activity on the strain of C. albicans, with the second extract showing greater power of action on the yeast. Therefore, extracts from Apis melífera L. and Caryocar brasiliense showed anti C. albicans activity, while those from Morus alba L., Morinda citifolia L. and Annona muricata L. did not.